Learner-Centered Pedagogy in Elementary Education: A Qualitative Study of Grade 4 Classroom Practices at Planas Integrated School - TABIANO, MARYJANE; Martin, Matronillo (Studies in Technology and Education, 2026)
Learner-centered pedagogy has become a central approach in contemporary education as it promotes active participation, critical thinking, and meaningful learning experiences among students. In elementary education, the implementation of learner-centered teaching practices plays an essential role in supporting the cognitive, social, and emotional development of young learners. This study explored the learner-centered pedagogical practices employed by Grade 4 teachers and examined students’ learning experiences at Planas Integrated School. Using a qualitative case study design, data were gathered through semi-structured interviews with teachers, focus group discussions with students, classroom observations, and document analysis of lesson plans. Thematic analysis was used to identify recurring patterns and themes related to classroom practices and student engagement. The findings revealed that teachers employed collaborative learning activities, inquiry-based tasks, contextualized instruction, and reflective discussions to foster learner participation. These practices enhanced students’ behavioral, emotional, and cognitive engagement during classroom instruction. However, teachers also encountered challenges such as limited instructional resources, time constraints, and diverse learner needs. The study highlights the importance of institutional support and continuous teacher professional development in sustaining learner-centered pedagogy in elementary classrooms.